PERSPECTIVE OF TECHNOLOGY, ORGANIZATION, AND ENVIRONMENT (TOE) ON THE ADOPTION OF E-COMMERCE BY SME IN TANGERANG REGENCY - Maya Angela Natalia; Timotius Febry Christian (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study focuses on analyzing the technology, organization, and environment (TOE) factors that influence the adoption of e-commerce by SMEs in the fashion industry of Tangerang Regency. Utilizing a quantitative approach and structural equation modeling (SEM) analysis through SEM-PLS software, this research aims to investigate how these factors interact and impact the adoption of e-commerce technology. Data for the study were collected via an online questionnaire using Google Forms, distributed to active SMEs that primarily utilize the Shopee platform for their sales channels. A total of 210 responses were successfully gathered, representing the SME population within the fashion industry of Tangerang Regency. The findings indicate that technology factors, including aspects such as relative advantage and compatibility, significantly influence e-commerce adoption. Organizational factors, encompassing organizational readiness and top management support, also have a substantial impact on e-commerce adoption. Environmental factors, which include competitive pressure and vendor support from e-commerce platforms, contribute positively to the adoption of e-commerce. These findings provide a deeper understanding of the key factors affecting SMEs' adoption of e-commerce, particularly in the fashion sector and within the geographic context of Tangerang Regency. The implications of this research highlight the importance for SMEs to leverage TOE factors in strategizing the adoption of e-commerce technology to enhance business performance and capitalize on the vast potential of the digital market.